Karakteristik Sumberdaya Ikan di Situ Gede, Tasikmalaya, Jawa Barat - Ni Komang Suryati; S. Sawestri; Dina Muthmainnah (Seminar Nasional Lahan Suboptimal, 2019)
Suryati NK, Sawestri S, Muthmainnah D. 2019. Fish resources characteristic in Situ Gede, Tasikmalaya, West Java. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 468-477. Palembang: Unsri Press.Situ Gede is one of the seven reservoirs in the Tasikmalaya City that has a function as fish resources, water resources, and tourism destination. Information regarding the characteristics of fish resources in the waters is still limited. This study aims to determine the characteristics of fish resources in Situ Gede. The results showed that the types of fish caught were tilapia (Oreochromis mossambicus), tawes (Barbonymus gonionotus) and snakehead (Channa striata). The fishing gears used are hook and line, cast net, and gill net. Based on the calculation of the fish stock at Situ Gede using the swept-area method, it has 16,404.89 kg of fish stock with area 74 ha. The composition of the fish caught during the study was 90% tilapia, 5% tawes, and 5% snakehead, with a total of 10 kg/catch. Fish resources in Situ Gede can be increased through restocking activities.Keywords: fish resources, Situ Gede, Tasikmalaya